Sustainability Risk Diffusion Through Clean Energy, Transition Risk, and ESG Market Connectedness in Malaysia - Rinda Siaga Pangestuti; Roszy Non; Erwin Susanto Sadirsan (AIBPM Publisher, 2026)
Climate change and the global low-carbon transition have intensified sustainability-related risks across financial markets, yet evidence on how such risks diffuse into emerging Asian economies remains limited. This study examines the dynamic connectedness and volatility spillovers among the NASDAQ Clean Edge Green Energy Index (CELS), the Transition Risk Index (TRI), and Malaysia's FTSE4Good Bursa Malaysia Index (F4GBM) during 2019-2025. This quantitative econometric study applies a hybrid framework combining the Dynamic Conditional Correlation-Generalized Autoregressive Conditional Heteroskedasticity (DCC-GARCH) model and the Diebold–Yilmaz connectedness index to daily returns. The results show that CELS is a persistent net transmitter of volatility, TRI is a policy-sensitive net receiver, and F4GBM alternates between absorbing and transmitting shocks. The total connectedness index rises from about 4% in late 2023 to above 8% by mid-2025, signaling deeper integration between climate-related risks and ESG market performance. The study concludes that investors should incorporate transition-risk indicators into diversification and hedging strategies, while policymakers should strengthen ESG disclosure, green taxonomies, and macroprudential climate-finance governance.